Association Between Historical Redlining and Access to High-Volume Hospitals Among Patients Undergoing Complex Cancer Surgery in California - Khalil, Mujtaba; Munir, Muhammad Musaab; Woldesenbet, Selamawit; Katayama, Erryk; Diaz, Adrian; Chen, JC; Obeng-Gyasi, Samilia; Pawlik, Timothy M. (Annals of surgical oncology, 2024)
Background We sought to determine the impact of historical redlining on travel patterns and utilization of high-volume hospitals (HVHs) among patients undergoing complex cancer operations. Methods The California Department of Health Care Access and Information database was utilized to identify patients who underwent esophagectomy (ES), pneumonectomy (PN), pancreatectomy (PA), or proctectomy (PR) for cancer between 2010 and 2020. Patient ZIP codes were assigned Home Owners’ Loan Corporation grades (A: ‘Best’; B: ‘Still Desirable’; C: ‘Definitely Declining’; and D: ‘Hazardous/Redlined’). A clustered multivariable regression was used to assess the likelihood of patients undergoing surgery at an HVH, bypassing the nearest HVH, and total real driving time and travel distance. Results Among 14,944 patients undergoing high-risk cancer surgery (ES: 4.7%, n = 1216; PN: 57.8%, n = 8643; PD: 14.4%, n = 2154; PR: 23.1%, n = 3452), 782 (5.2%) individuals resided in the ‘Best’, whereas 3393 (22.7%) individuals resided in redlined areas. Median travel distance was 7.8 miles (interquartile range [IQR] 4.1–14.4) and travel time was 16.1 min (IQR 10.7–25.8). Overall, 10,763 (ES: 17.4%; PN: 76.0%; PA: 63.5%; PR: 78.4%) patients underwent surgery at an HVH. On multivariable regression, patients residing in redlined areas were less likely to undergo surgery at an HVH (odds ratio [OR] 0.67, 95% confidence interval [CI] 0.54–0.82) and were more likely to bypass the nearest hospital (OR 1.80, 95% CI 1.44–2.46). Notably, Medicaid insurance, minority status, limited English-language proficiency, and educational level mediated the disparities in access to HVH. Conclusion Surgical disparities in access to HVH among patients from historically redlined areas are largely mediated by social determinants such as insurance and minority status.